Persuasive techniques in internet romance scams / Tan Hooi Koon - Tan, Hooi Koon (2014)
In 2012 alone, the Royal Malaysian Police (RMP) reports that Internet Romance Scams (IRS) have caused a loss of RM32.09million. Using romance and love as bait, romance scammers entice their targets into a romantic relationship before persuading them to give money; hence causing victims to also suffer psychological and emotional trauma. This qualitative case study examines a total of 15 scammer e-mails taken from one successfully closed IRS case obtained from RMP to determine (1) how the scammer’s credible identity is established, (2) how the target’s emotional responses are aroused, and (3) how the fraudulent scheme is diachronically developed; focusing on Aristotle’s means of persuasion: ethos (credibility), pathos (emotions) and logos (reason). Briefly, at the beginning, the scammer established a credible identity by claiming to be a religious, reputable and honourable person. His credibility was enhanced through the use of evidence, reason and well-structured arguments to justify his claims or behaviour (e.g. request for money). Then, as an ideal lover, he developed an intense emotional bond with the target through the repetitive use of language that arouses positive emotions; but to obtain money from her, the scammer invoked her negative emotions using a distressed lover identity. This research also discusses the similarity between the development of the IRS and non-fraudulent romantic relationships as well as the possibility of IRS being a form of intimate partner violence. This research concludes with recommendations to reduce the number of IRS, along with the limitations of the research as well as the recommendations for future studies. Keywords: Internet romance scams (IRS), persuasion, influence tactics, credible identity, emotional appeals, online communication, romantic relationship development, romancing strategies, discourse analysis